How physical interaction with insight problems affects solution rates, hint use, and cognitive load. - Chuderski, Adam; Jastrzębski, Jan; Kucwaj, Hanna (British Journal of Psychology, 2021)
So‐called insight problems are widely studied because they tap into the creative thinking that is crucial for solving real problems. However, insight problems are typically presented in static formats (on paper, computer) that allow no physical interaction with the problem elements, whereas such an interaction might in fact reduce the load on limited cognitive resources, such as working memory (WM) capacity, thereby facilitating solutions. To test this proposition, 124 young adults were allowed to interact physically with nine established insight problems, while another 124 people attempted to solve these problems using paper and pencil. Additionally, hints were provided for three problems that typically no‐one solves. No general facilitating effect of physical interaction was found, with only one problem clearly benefitting from it. Furthermore, making use of hints was actually hindered by physical interaction. No difference in perceived task load and correlation with WM capacity was observed between the formats, and subjective ratings of insight were virtually unaffected by presentation format. Overall, physical interaction minimally affected insight problem‐solving, which appears to rely strongly on internalized cognitive processing involving WM.